Perusing Learning Challenges in the Digital Era: Between Qur’ānic Concepts and Contemporary Education - Nur Fazwanis Binti Othman; Muhammad Fawwaz Bin Muhammad Yusof (USIM Press, 2024)
Journal of Quran Sunnah Education and Special Needs (JQSS) Volume 7 Issue 2 Page (52-59)